2021
DOI: 10.14569/ijacsa.2021.0121275
|View full text |Cite
|
Sign up to set email alerts
|

Automated Telugu Printed and Handwritten Character Recognition in Single Image using Aquila Optimizer based Deep Learning Model

Abstract: Machine printed or handwritten character recognition becomes a major research topic in several real time applications. The recent advancements of deep learning and image processing techniques can be employed for printed and handwritten character recognition. Telugu character Recognition (TCR) remains a difficult task in optical character recognition (OCR), which transforms the printed and handwritten characters into respective text formats. In this aspect, this study introduces an effective deep learning based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…For the purpose of automating the recognition of printed and handwritten Telegu characters inside a single image, Sonthi et al [ 57 ] suggested an AO based deep learning model. To prepare the images for analysis, an adaptive fuzzy filtering method was used and the character segmentation techniques to isolate useful areas.…”
Section: Related Work On Classical Ao and Its Improved Variantsmentioning
confidence: 99%
“…For the purpose of automating the recognition of printed and handwritten Telegu characters inside a single image, Sonthi et al [ 57 ] suggested an AO based deep learning model. To prepare the images for analysis, an adaptive fuzzy filtering method was used and the character segmentation techniques to isolate useful areas.…”
Section: Related Work On Classical Ao and Its Improved Variantsmentioning
confidence: 99%
“…Aquila optimization using the adaptive fuzzy filtering [80] and multi-objective mayfly optimization with deep learning (MOMFO-DL) [81] techniques aims to detect and recognize handwritten Telugu characters. Character recognition is performed in the presence of both handwritten and printed text that coexist in the same document.…”
Section: Text Recognitionmentioning
confidence: 99%
“…Individuals exhibit diverse writing styles, making it difficult to create a universal model that accurately recognizes all variations. Factors such as the size, slant, and spacing of characters further contribute to the complexity of the recognition process [47].…”
Section: Challenges Of Handwriting Recognitionmentioning
confidence: 99%